The accuracy of 3D kinetic and kinematic data used for joint loading analysis in skiing and snowboarding - - Klous, M.; Schwameder, H.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Almost 50% of all skiing accidents in men and more then 70% of all skiing accidents in women concerned the lower extremities. In snowboarding about a third of all accidents concerned the lower extremities in both men and women (Burtscher et al., 2003). These high percentages afford systematic research to determine joint loading on the lower extremities in skiing and snowboarding. However, so far only rough estimations of joint loading are reported (van den Bogert et al., 1999; Quinn & Mote, 1992). More precise values would be possible by inverse dynamic analyses. These require representative 3D kinetic and kinematic data which serve as input for the inverse dynamic model to calculate the loading parameters. Therefore, the goal of this presentation is to give an overview and validation of the methodological procedures used in this study to collect and analyse 3D kinetic and kinematic data to determine the loading parameters.